2022
DOI: 10.3389/fendo.2022.1036517
|View full text |Cite
|
Sign up to set email alerts
|

A spatiotemporal steroidogenic regulatory network in human fetal adrenal glands and gonads

Abstract: Human fetal adrenal glands produce substantial amounts of dehydroepiandrosterone (DHEA), which is one of the most important precursors of sex hormones. However, the underlying biological mechanism remains largely unknown. Herein, we sequenced human fetal adrenal glands and gonads from 7 to 14 gestational weeks (GW) via 10× Genomics single-cell transcriptome techniques, reconstructed their location information by spatial transcriptomics. Relative to gonads, adrenal glands begin to synthesize steroids early. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 61 publications
3
5
0
Order By: Relevance
“…As 3β-hydroxysteroid dehydrogenase type 2/ HSD3B2 is effectively a gatekeeper to glucocorticoid and mineralocorticoid biosynthesis ( Figure 3D ), we investigated HSD3B2 expression across time series data. Although a potential transiently higher expression was seen at 8wpc in bulk RNA-Seq data ( Supplemental Figure 7 ), as reported previously ( 33 , 35 , 39 ), single-cell transcriptomic data showed overall greater increase in HSD3B2 across time, with the highest levels in the DZ cluster at 19wpc ( Figure 3E ). A similar graded increase in CYP21A2 (encoding 21-hydroxylase) and CYP11B1 (encoding 11β-hydroxylase type 1) was seen ( Figure 3E ).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…As 3β-hydroxysteroid dehydrogenase type 2/ HSD3B2 is effectively a gatekeeper to glucocorticoid and mineralocorticoid biosynthesis ( Figure 3D ), we investigated HSD3B2 expression across time series data. Although a potential transiently higher expression was seen at 8wpc in bulk RNA-Seq data ( Supplemental Figure 7 ), as reported previously ( 33 , 35 , 39 ), single-cell transcriptomic data showed overall greater increase in HSD3B2 across time, with the highest levels in the DZ cluster at 19wpc ( Figure 3E ). A similar graded increase in CYP21A2 (encoding 21-hydroxylase) and CYP11B1 (encoding 11β-hydroxylase type 1) was seen ( Figure 3E ).…”
Section: Resultssupporting
confidence: 85%
“…It is well established that the FZ synthesizes and releases large amounts of DHEA(-S), due to a relative lack of the enzyme 3 β-hydroxysteroid dehydrogenase type 2 (3β-HSD2, encoded by HSD3B2 ) and likely high expression of genes encoding enzymes needed for androgen biosynthesis (i.e., CYP17A1 , POR , CYB5A ). Although a transient wave of HSD3B2 /3β-HSD2 expression has been shown at around 8–9wpc ( 33 , 35 , 39 ), evidence is still emerging as to when the necessary enzymes for glucocorticoid (e.g., cortisol) and mineralocorticoid (e.g., aldosterone) synthesis are expressed during human adrenal development, especially into the second trimester ( 34 , 35 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from 7-8 weeks, these somatic progenitors bifurcated into two different developmental paths, one of which is embryonic Sertoli progenitors (marked by SRY , similar to the “early supporting gonadal cells” in Garcia-Alonso et al's work 74 ) and then became fetal SC 79 . The rest path, on the contrary, led to embryonic/fetal interstitial progenitors (marked by ARX and TCF21 , also called Leydig precursor cells by Li et al 73 and called somatic progenitor by Wang et al 84 ), and finally part of the fetal interstitial progenitors became fetal Leydig cells (marked by HSD3B2 and CYP17A1 , also called differentiated LC by Li et al 73 ) 79 , 80 . During the development of prenatal interstitial/Leydig lineage, the enriched molecular pathways altered from “extracellular matrix”/ “cell adhesion” to “steroid biosynthesis”.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it was CYP17A1-negative fetal interstitial cells that might finally pass the birth and finally become the common progenitors of adult LC and PTM 79 . Regarding EC, although some studies proved the early appearance of EC in prenatal male gonad 73 , 84 , so far there have been few studies that focused on EC development. Like the previous murine studies 85 , 86 , scRNA-seq data on human the fetal testis also revealed two distinct types of macrophages in the fetal testis, of which one is named SIGLEC15 + fetal testicular macrophages (osteoclast-like) and the other is TREM2 + fetal testicular macrophages (microglia-like) 74 .…”
Section: Resultsmentioning
confidence: 99%